LGE-MRI in the Assessment of Left-ventricular Remodelling in Myocarditis - Yuan, Wei-Feng; Zhao, Xin-Xiang; Sun, Wen-Jing; Wu, Shao-Ping; Liu, Ya-Bin; Tang, Xi (Current Medical Imaging, 2019)
Background: The exact morbidity of myocarditis is unknown, as the treatment is generally delayed in virtue of misdiagnosis or missed diagnosis. Aim: The aim of this study was to identify prognostic factors of left-ventricular remodeling on CMRI performed in patients with pathological proven myocarditis. Methods: Sixty-two cases with various presentations of myocarditis (39 cases with heart failure; 23 cases with arrhythmias) were selected. All patients, who underwent coronary angiography, endomyocardial biopsy, were divided into positive-remodeling and negative-remodelling groups to analyse LGE and cardiac cine parameters at presentation and subsequent to 3 months. Results: Comparison of two subgroups in CMRI is as follows: positive LGE (65.6% vs. 86.7%; p<0.05), LVEF (41.3±14.8% vs. 37.6±10.1%; p=0.62), (25.7±2.0% vs. 24.0±2.5%; p=0.81), (44.5±3.9mm vs. 46.3±5.4mm; p=0.76), (129.1±8.5ml vs. 135.3±12.2ml; p=0.26), (74.8±7.3ml vs. 79.1±10.0ml; p=0.55), (52.0±5.7g vs. 49.6±6.5g; p=0.71), (34.9±3.5ml vs. 32.4±6.2ml; p=0.68), (3.8±0.7L/min vs. 3.1±0.5L/min; p=0.64), (2.9±0.6L/min*m2 vs. 2.7±0.5L/min*m2; p=0.79). Conclusion: LGE-MRI is rewarding as an independent predictor in left-ventricular positive and negative remodelling of myocarditis.
Keywords: remodelling